Transitional justice and temporal parameters: built-in expiration dates? - Horne, Cynthia M. (International journal of transitional justice, 2020)
Temporal assumptions associated with personnel reforms, such as lustration and public disclosure programs, both prescribe the optimal timing for the onset of measures and proscribe a long duration for such measures. In the context of the post-communist transitions, these assumptions suggested that lustration and public disclosures should be enacted as soon as possible after a regime transition, with the legitimacy, motives, and legal appropriateness of delayed measures being questioned. In terms of duration, personnel reforms should have fixed time limits, often suggested as no more than a decade. This article critically explores the evolution of these temporal assumptions through an examination of the legal rulings, intergovernmental policies, and recommendations of the Parliamentary Assembly of the Council of Europe, the European Court of Human Rights, and the Venice Commission. The article illustrates the tension between the continued use of the measures by some post-communist states and international rulings signalling their expiration.